The Influence of Competence, Service Performance Through A Service Quality Over Midwife units in Banten Hospital - Theresia Sri Lestari; CSP Wekadigunawan; Endang Ruswanti (Penerbit Kemala Indonesia, 2020)
The main problem in this study is faced by the Indonesian nation is health problems in the group of mothers and babies. Here, the patients' perceptions have competence of midwives, a service performance were needed to assess the quality of service in the midwifery unit at Banten Hospital (RSUD Banten). Thus, there is an effect of perceptions of the quality of midwifery services on patient satisfaction at the Barru Sulawesi Hospital inpatient. The purpose of this study was to analyse the influence of the competence of midwives, the performance of midwifery services on the quality of service in the midwifery inpatient unit Banten Hospital (RSUD Banten). In this study, the quantitative research method involved a sample of 150 people. The data were processed using the Path statistical test (path analysis) of the Amos program. The results showed that there was no positive effect of midwifery competence on the quality of midwifery services, there was a positive effect of midwifery competence on the performance of midwifery services with a positive effect of midwifery service performance on the quality of midwifery services. It was found that patients in the midwifery ward did not directly experience the quality of midwifery services through the competence of midwives. The competence of midwives first affects the performance of midwifery services and then affects the quality of midwifery services. Improving the quality of midwifery services is a top priority due to patient perceptions of the good quality of midwifery services will have an impact on the good performance of midwifery services and the level of competency of midwives in hospitals. Managerial implications become input for the midwifery inpatient room of Banten Hospital, the need to improve the competence of midwives in techniques for better education and midwifery services through training and minimizing deficiencies to improve the quality of midwifery services according to patient expectations.